Five anti-inflammatory plant species of the Libellus de Medicinalibus Indorum Herbis from Mexico, 1552: A botanical, chemical and pharmacological review - López-Miranda, Dulce Yehimi; Reyes Chilpa, Ricardo; Magos, Gil A.; Ávila Acevedo, José Guillermo; Guzmán-Gutiérrez, Silvia Laura; Martínez-Ambriz, Emmanuel; Campos-Lara, María Guadalupe; Osuna-Fernández, Helia Reyna; Jiménez-Estrada, Manuel (Instituto de Ecología, A.C., 2023)
Background and Aims: The Libellus de Medicinalibus Indorum Herbis (Little Book of the Medicinal Herbs of the Indians) includes 185 beautifully illustrated plants, 131 interpreted to species. Only some have been investigated regarding their attributed properties. Therefore, we selected six plants used as anti-inflammatories. The objectives of this work were to corroborate their botanical identity and to determine if contemporary chemical and pharmacological information supports their ancient therapeutic applications.Methods: The illustrations of the chosen plants were compared with specimens from the MEXU Herbarium to propose their possible taxonomic identity. The phytochemistry and anti-inflammatory activity of these species were reviewed in databases.Key results: The six plants selected from the Codex correspond to five species, since we consider that tetzmitl (Folium 13r) and texiyotl (Folium 22v) plants are the same species: Sedum dendroideum. Extracts from the leaves of S. dendroideum have shown anti-inflammatory activity in different pharmacological models due to derivatives of the flavonoid kaempferol, which supports its ancient medical applications to treat swollen face, eyes, and mouth. In Folium 48v, tzihuac copalli and tlacoecapatli are prescribed when “the vein punctured by the phlebotomy swells.” We agree they are Bursera bipinnata and Litsea glaucescens, respectively. To date, their possible anti-inflammatory properties have not been investigated, but other related species do present these. The Folium 22v recommends tememetla and tequixquiçacatl to relieve inflamed mouth. We corroborate that they are Echeveria gibbiflora and Distichlis spicata, respectively. These species do not have chemical-pharmacological studies.Conclusions: The bibliographic review suggests that anti-inflammatory properties attributed to S. dendroideum in the Codex have chemical and pharmacological support. Chemotaxonomic and pharmacological information suggests that B. bipinnata and L. glaucescens could bear these attributes and should be investigated experimentally. These three species are still used as anti-inflammatory in contemporary traditional medicine.